Cd-doped Ag2O/BiVO4 visible light Z-scheme photocatalyst for efficient ciprofloxacin degradation. Issue 55 (13th December 2022) - De, Arup Kumar; Kumar, Uttam; Jatav, Neha; Sinha, Indrajit
Abstract : Foreign element doping can produce new photocatalysts with different band edge positions and adsorption properties. Abstract : Foreign element doping can produce new photocatalysts with different band edge positions and adsorption properties. A composite of such a doped semiconductor with another component should enhance its photocatalytic properties towards a target substrate. The present investigation used a simple hydrothermal protocol to prepare Cd-doped Ag2 O nanoparticles. The Cd-doping of Ag2 O nanoparticles changed its valence band maximum position from 0.8 eV (for undoped Ag2 O nanoparticles) to 2.67 eV with a slight narrowing of the Ag2 O bandgap. A combination of DFT calculation and XRD results showed that the dopant Cd substituted Ag in the Ag2 O lattice. The doped material is an effective photocatalyst for ciprofloxacin degradation but with poor recyclability. The joining of a BiVO4 part to the Cd-doped Ag2 O nanostructures gave a composite with improved photocatalytic activity and recyclability towards ciprofloxacin degradation. DFT calculations showed that BiVO4 has a higher oxygen affinity than Cd-doped Ag2 O. The XPS characterization of the composite and appropriate active species scavenger experiments demonstrated a Z-scheme mechanism. Superoxide radicals play a critical role in CIP degradation.